Tuberculosis: a Human Rights approach - Ugarte-Gil, César Augusto (2009)
Tuberculosis is a disease affceting manking form very early ages, and despite the availability of appropriate therapy for most cases, it is a disease that increases the gap between the rich and the poor.Unfortunately, the efforts to fight this disease have not been focused on its socio-economic nature, leading these strategies and resources to fall short. This paper tries to show if an approach based on Human Rights is able to complement biomedical and public health measures in the fight against Tuberculosis.